2017
DOI: 10.1037/pla0000053
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a two-day child parent relationship therapy training on attitude, knowledge, and skills.

Abstract: This study measured the impact of a 2-day Child Parent Relationship Therapy (CPRT) training for therapists who want to facilitate parent CPRT groups, using an adapted version of the Play Therapy Attitude, Knowledge, and Skills Survey (PTAKSS). The primary author adapted this instrument (CPRT-PTAKSS) to measure the objectives of CPRT, with permission from the author and a factor analysis was conducted. Paired samples t tests were then conducted between the pre-and posttest scores for each of the subscales. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…These reliability coefficients indicate a high degree of reliability of obtained results for the instrument. The reliability results presented are consistent with the findings from other studies of play therapy (Perryman et al, 2017; Thanasiu et al, 2018).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…These reliability coefficients indicate a high degree of reliability of obtained results for the instrument. The reliability results presented are consistent with the findings from other studies of play therapy (Perryman et al, 2017; Thanasiu et al, 2018).…”
Section: Resultssupporting
confidence: 90%
“…the instrument. The reliability results presented are consistent with the findings from other studies of play therapy (Perryman et al, 2017;Thanasiu et al, 2018).…”
Section: Research Questionsupporting
confidence: 90%
See 1 more Smart Citation
“…This category included articles related to providing play therapists with more knowledge on different areas and articles related to specific training or teaching practices for play therapists. For example, one article discussed different play therapy approaches when working with children with intellectual disabilities (Astramovich, Lyons, & Hamilton, 2015) and another article under this category discussed the effectiveness of a 2-day CPRT training on therapists (Perryman, Christian, & Massengale, 2017). From the 74 articles identified, 23 articles were research based and 51 articles were nonresearch based.…”
Section: Resultsmentioning
confidence: 99%
“…Fortunately, CTRT has shown great adaptability with its training and application. For instance, Perryman et al, (2017) found that 2 days of training, as opposed to the five sessions suggested by Landreth and Bratton (2006), can be effective with professionals familiar with working with youth. Adaptations in the application and supervision processes have also been implemented successfully to meet the caregiver’s needs and schedules (Morrison & Helker, 2010; Socarras et al, 2015).…”
Section: Pal Model For Speech–language Pathologists and Play Therapistsmentioning
confidence: 99%